ANALISIS PENERAPAN K3 DAN EFEKTIFITAS PELATIHAN K3 DI PT IHM KALIMANTAN TIMUR - Diah Rakhmah Sari; Alfonsus Bernyanto Gois, Dadang Imam Ghozali (Jurnal Kesehatan, 2024)
The role of labour in economic development is significant, and thus the achievement of occupational health and safety (OHS) is a fundamental necessity for workers. One such effort is the implementation of OHS programmes and OHS training, which serves to ensure the safety of the workforce. The objective of this study is to evaluate the implementation of OHS and the efficacy of OHS training at PT IHM. This research was conducted at PT IHM, which is located in the Sepaku sector of Penajam Paser Utara Regency. It employed interview and questionnaire methods to survey 60 employees of PT IHM. The data was subjected to validity and reliability tests and descriptive analysis. Overall, it can be concluded that the application of occupational health at PT IHM has been effective. Over 90% of employees agree or strongly agree with all statements about occupational health, while only 1-7% of respondents disagree. The implementation of occupational safety in the workplace at PT IHM has also been successful. In response to all statements regarding the application of occupational safety, 99% of respondents indicated agreement or strong agreement, while only 1% expressed disagreement with the assertion that work equipment is in good condition and suitable for use. The implementation of OHS training has also been found to be effective, with more than 90% of employees agreeing and strongly agreeing that OHS training has an effect on the level of work accidents.